Surgical treatment of aggressive pituitary adenomas and pituitary carcinomas - Buchfelder, Michael; Schlaffer, Sven-Martin (Reviews in Endocrine & Metabolic Disorders, 2020)
Surgery of aggressive pituitary adenomas and pituitary carcinomas is part of the interdisciplinary management of these difficult to treat tumors. Invasion, giant size and unusual, asymmetric extent of these tumors frequently require modifications or extensions of the standard approaches for transsphenoidal and transcranial surgery. Frequently, only debulking procedures can be performed. In aggressive and hormone secreting adenomas, the remission rates achieved by surgery alone are relatively poor and adjuvant medical treatments or irradiation are needed. Safe resection of as much tumor as possible and symptomatic control is aimed at, rather than remission. Many procedures are required for rapid progression of lesions or recurrences, in order to extend the survival of the patients. Metastases of pituitary carcinomas within the cranial cavity or spine can be attacked. Since they can occur anywhere in the brain or spinal canal they require the entire battery of neurosurgical approaches. Unfortunately, in this group of pituitary tumors, the complication rates are higher than in primary operations of enclosed adenomas. The respective techniques with their facilities and limitations are reviewed in this article.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Aggressive growth; Cavernous sinus; Interdisciplinary management; Invasive adenoma; Pituitary carcinomas; Transcranial surgery; Transsphenoidal surgery